Physicochemical and Storage Characteristics of Pork Tteokgalbi Treated with Watermelon Radish Powder - Ye-Sol Kim; Jae-Joon Lee; Inyong Kim; Daeung Yu; Jung-Heun Ha (Applied Sciences, 2022)
Here, we investigated the physicochemical and storage characteristics of Tteokgalbi using n-3 fatty acid-enriched pork (n-6/n-3 ratio: 3.220) and explored the effects of treatment with watermelon radish powder (W; 0–4%). Tteokgalbi groups were prepared with 0% W (control (CON)), 1% W (W1), 2% W (W2), 4% W (W3), or 0.05% ascorbic acid as a reference (REF) treatment. W addition to Tteokgalbi increased the moisture and ash contents and water-holding capacity, but reduced cooking loss. W-prepared Tteokgalbi had markedly decreased L* (brightness) and increased b* (yellowness) values, but significantly increased a* (redness) values. W treatment markedly altered the textural properties of Tteokgalbi by improving the hardness and chewiness (W3 treatment), but decreasing springiness (W3) and brittleness (W2 and W3). W addition dose-dependently increased the total polyphenol and flavonoid contents, thereby increasing the 2,2-diphenyl-1-picrylhydrazyl and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical-scavenging activities of Tteokgalbi over 7 days in cold storage. W-treatment Tteokgalbi decreased the pH slightly (compared to CON treatment) and significantly attenuated the induction of 2-thiobarbituric acid, volatile basic nitrogen, and total microbial counts during 7 days in cold storage. Therefore, W may be a suitable food antioxidant that can act as a natural radical scavenger in Tteokgalbi prepared from n-3 fatty acid-enriched pork.